2019
DOI: 10.15421/011917
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tillage system and fertilization on corn yield and water use efficiency in irrigated conditions of the South of Ukraine

Abstract: Efficient water management in agriculture is an important part of the general programme on water resources preservation. This study is devoted to the determination of the effects of soil processing system and mineral fertilization on the water use efficiency and productivity of grain corn (Zea mays Linnaeus, 1753). The trials were conducted in 2017–2018 on irrigated land in the South of Ukraine. The field experiments were carried out on the experimental plots of the Institute of Irrigated Agriculture of the NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…Результати досліджень свідчать, що найвищий урожай зерна кукурудзи та найбільш ефективне використання вологи забезпечувала технологія вирощування з обробітком дисковим знаряддям на глибину 8-10 см у системі диференційованого обробітку ґрунту в сівозміні на фоні максимальної дози мінеральних добрив N180P60. Такий агротехнологічний варіант забезпечив урожайність зерна кукурудзи за умови проведення досліджень 2017 та 2018 років на рівні, відповідно 14,51 та 14,59 т/га [22,23].…”
Section: вступunclassified
“…Результати досліджень свідчать, що найвищий урожай зерна кукурудзи та найбільш ефективне використання вологи забезпечувала технологія вирощування з обробітком дисковим знаряддям на глибину 8-10 см у системі диференційованого обробітку ґрунту в сівозміні на фоні максимальної дози мінеральних добрив N180P60. Такий агротехнологічний варіант забезпечив урожайність зерна кукурудзи за умови проведення досліджень 2017 та 2018 років на рівні, відповідно 14,51 та 14,59 т/га [22,23].…”
Section: вступunclassified
“…Низка науковців відзначають, що за допомоги різних способів основного обробітку ґрунту можна дієво впливати на формування водного режиму ґрунтів, а наслідком цього є збільшення урожайності культури, яке забезпечується ефектом від використання ресурсу вологи [20,21,24].…”
Section: вступunclassified
“…It varies from 0.55 (Tanzania) to 3.33 kg/m 3 (USA) [39]. Vozhehova et al [40] studied corn production on irrigated land in the south of Ukraine. They found that the lowest water-use productivity (0.5149 kg/m 3 ) was provided by disk cultivation (depth of 12 to 14 cm) and zero fertilizer.…”
Section: Sismentioning
confidence: 99%